2022
DOI: 10.1186/s12913-022-08175-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety culture as perceived by operating room professionals: a mixed-methods study

Abstract: Background Routine assessments of patient safety culture within hospitals have been widely recommended to improve patient safety. Experts suggested that mixed-methods studies can help gain a deeper understanding of the concept. However, studies combining quantitative and qualitative approaches exploring patient safety culture are still lacking. This study aimed to explore patient safety culture as perceived by operating room professionals of two university hospitals in Sousse, Tunisia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
(45 reference statements)
1
16
0
Order By: Relevance
“…As managers and staff in the operating room, adopting the broken window theory can help prevent surgical accidents and minimize their impact on operations. [24–26]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As managers and staff in the operating room, adopting the broken window theory can help prevent surgical accidents and minimize their impact on operations. [24–26]…”
Section: Discussionmentioning
confidence: 99%
“…As managers and staff in the operating room, adopting the broken window theory can help prevent surgical accidents and minimize their impact on operations. [24][25][26] In China, the adoption of micro-class teaching mode has been relatively recent. Hu et al [27] first introduced the concept of micro-class in China in Guangdong Province in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed a worrying perception among healthcare professionals in surgical departments stemming from the absence of a robust patient safety culture (Aouicha et al, 2022). Standardised resources and tools are recommended to monitor factors potentially harmful to patients (Turley et al, 2023;Urban et al, 2021).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…There are many studies on a safety culture assessment in different contexts (operating rooms, emergency services). Such studies are found in four European countries, including Croatia, Hungary, Spain, Sweden (Granel-Giménez et al, 2022), Tunisia (Aouicha et al, 2022) and Portugal (Vinagre & Marques, 2018). However, the area of maternal and obstetric health has not been adequately evaluated, as it is a context that involves specialized care to two individuals (mother and baby) and is focused on both health promotion and prevention of complications to minimize the double risk of maternal and fetal morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%